ASEAN and the Dynamics of Resistance to Sovereignty Violation: The Case of the Third Indochina War (1978–1991). (August 2015) - Southgate, Laura
This article investigates the history of ASEAN's relationship to external intervention in regional affairs. It addresses a specific question: What was the basic cause of the success of ASEAN resistance to the Vietnamese challenge to ASEAN's sovereignty from 1978-1991? ASEAN's history is understood in terms of a realist theoretical logic, in terms of the relationship between an ASEAN state with the most compelling interests at stake in a given issue, which I call a 'vanguard state, ' and selected external powers. Using the Third Indochina War (1978–1991) as a case study, this article contends that ASEAN's ability to resist violations to the sovereignty of Thailand from a Soviet-backed Vietnam is a consequence of high interest convergence between Thailand, and a designated external power, China.